Italy : Financial Sector Assessment Program; Detailed Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies; Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses a Detailed Assessment of the Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies-Securities Regulation for Italy. The paper discusses that in the area of securities regulation, the objectives and responsibilities of the two supervisory authorities, namely Consob and the Banca d'Italia (BI), and the modalities of cooperation between them, are clearly established in the 1998 Consolidated Law. An area where further clarity may be warranted concerns the practical modalities of exchanging information with other domestic institutions.